2009
DOI: 10.1021/ef800648y
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Lipase on Fe3O4 Nanoparticles as Biocatalyst for Biodiesel Production

Abstract: In this work, magnetic Fe 3 O 4 nanoparticles treated with (3-aminopropyl)triethoxysilane were used as immobilization material. Lipase was covalently bound to the amino-functionalized magnetic nanoparticles by using glutaraldehyde as a coupling reagent with the activity recovery up to 70% and the enzyme binding efficiency of 84%. The binding of lipase to the magnetic particles was confirmed by enzyme assays, transmission electron microscopy, X-ray powder diffraction, and Fourier transform infrared spectra. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
120
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(127 citation statements)
references
References 35 publications
7
120
0
Order By: Relevance
“…Due to steric hindrance effect, the activity of the immobilized lipase ebbing [27]. Xie et al achieved the maximum immobilization efficiency and activity recovery like above 80% and 65% at 10% glutaraldehyde concentration by lipase (Lipozyme-TL) immobilized on APTES-Fe3O4 [5]. This study achieved the maximum immobilization efficiency and activity recovery were obtained 97% and 86% at same concentration of glutaraldehyde by lipase (NS81006) immobilized on APTES-Fe3O4 while lipase immobilized on MPTMS-Fe3O4 also attained maximum immobilization efficiency and activity recovery.…”
Section: Effect Of Glutaraldehyde Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to steric hindrance effect, the activity of the immobilized lipase ebbing [27]. Xie et al achieved the maximum immobilization efficiency and activity recovery like above 80% and 65% at 10% glutaraldehyde concentration by lipase (Lipozyme-TL) immobilized on APTES-Fe3O4 [5]. This study achieved the maximum immobilization efficiency and activity recovery were obtained 97% and 86% at same concentration of glutaraldehyde by lipase (NS81006) immobilized on APTES-Fe3O4 while lipase immobilized on MPTMS-Fe3O4 also attained maximum immobilization efficiency and activity recovery.…”
Section: Effect Of Glutaraldehyde Concentrationmentioning
confidence: 99%
“…Recently enzymatic transesterification of vegetable oils has appealed more attention due to the advantages of environmental friendliness and effectively converting both triglycerides and FFA * Corresponding author: duwei@tsinghua.edu.cn (free fatty acids) into FAME (fatty acid methyl esters) [4][5][6]. There are extensive studies related to immobilized lipase-mediated alcoholysis of vegetable oil for biodiesel production.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high cost of lipase makes enzymatic processes commercially unattractive. Therefore, immobilization of lipase has advantages over free lipase in terms of its reusability, its ease of removal from the reaction mixture and its adaptability to various engineering designs (Xie and Ma, 2009). Nevertheless, the high cost of com-mercial immobilized lipase due in part to the requirement for expensive support materials, makes production of biodiesel by this approach more expensive than that produced by chemical catalysis and so it is not economically viable.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent reaction rate and stability of the immobilized lipase were greatly improved after crosslinking. Xie and Ma (2009) reported that immobilized lipase on Fe 3 O 4 nanoparticles treated with 3-APTES was using as biocatalyst for biodiesel production via transesterification. The conversion of soybean oil to biodiesel fuels reached over 90% by the three-step addition of methanol when 60% immobilized lipase was employed.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic micro/nanoparticle lipases in different designs using various modifications of the core iron matrix and covalent linkages have been studied for catalyzing reactions in aqueous and non-aqueous media. Immobilization of lipase on Fe 3 O 4 treated with (3-aminopropyl) triethoxysilane (APTES) using glutaraldehyde as a coupling reagent was first reported for transesterification of soybean oil 17) and then with the use of immobilized lipase linked to the magnetic support by 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDAC). 18) Composite inorganic or biological polymers can improve magnetic micro/ nanoparticle-immobilized lipase stability by strengthening the core magnetic structures or modifying physical properties of the magnetic carriers, e.g.…”
mentioning
confidence: 99%